BRANDING AND REBRANDING - GROCERY MARKET PERSPECTIVE - Mróz-Gorgoń, Barbara (Acta Scientiarum Polonorum. Oeconomia, 2016)
The paper presents problems of branding and rebranding as strategies of brand image creation. The study focused on grocery market as an example. The article aims to analyze branding activities of the grocery market and to identify trends, as well as the reasons for rebranding actions and tactics. Brands host many qualities, some of them spiritual (i.e. values, mission) or virtual (i.e. logo). A change of image is one of the ways to regain or keep competitive advantage. Effective rebranding activities - those positively influencing brand image - must distinguish a brand from competition, increase brand awareness and be conform to company mission and strategy. The article is based on studies of national and foreign literature, as well as on results of authors' own primary studies (questionnaire and focus group interview).